Implication of Cord Blood for Cell-Based Therapy in Refractory Childhood Diseases - Lee, Young-Ho (Korean Society for Stem Cell Research, 2010)
Since cord blood (CB) contains hematopoietic stem cells as well as a mixture of multipotent stem cells, CB has the ability to give rise to hematopoietic, epithelial, endothelial and neural tissues. Recently, the application of cell-based therapy using CB has expanded its clinical utility, particularly, by using autologous CB in children with refractory diseases. This review focuses clinical and pre-clinical application of CB cell-based therapy for inherited metabolic diseases as well as tissue regenerations in neonatal hypoxic-ischemic encephalopathy, cerebral palsy, and juvenile diabetes.